2015
DOI: 10.3393/ac.2015.31.5.192
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors to Distinguish Between Patients With Noncomplicated Appendicitis and Those With Complicated Appendicitis

Abstract: PurposeRecently, randomized controlled trials have reported that conservative therapy can be a treatment option in patients with noncomplicated appendicitis. However, preoperative diagnosis of noncomplicated appendicitis is difficult. In this study, we determined predictive factors to distinguish patients with noncomplicated appendicitis from those with complicated appendicitis.MethodsA total of 351 patients who underwent surgical treatment for acute appendicitis from January 2011 to December 2012 were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…In clinical practice, diagnosis of complicated appendicitis rarely relies on a single individual CT feature, but on multiple CT features combined with clinical findings. In fact, there have been attempts to build diagnostic models for complicated appendicitis that combine both clinical and imaging findings (32,54). This study may contribute to future studies on diagnostic algorithms for complicated appendicitis by providing more comprehensive inclusion of CT features as potential predictors.…”
Section: Evidence-based Practice: Differentiating Complicated and Uncmentioning
confidence: 97%
“…In clinical practice, diagnosis of complicated appendicitis rarely relies on a single individual CT feature, but on multiple CT features combined with clinical findings. In fact, there have been attempts to build diagnostic models for complicated appendicitis that combine both clinical and imaging findings (32,54). This study may contribute to future studies on diagnostic algorithms for complicated appendicitis by providing more comprehensive inclusion of CT features as potential predictors.…”
Section: Evidence-based Practice: Differentiating Complicated and Uncmentioning
confidence: 97%
“…Complicated appendicitis is defined as acute appendicitis with associated peritonitis, rupture, gangrene, or intra-abdominal abscess (IAA) and accounts for 14%-55% of all cases of appendicitis [4]. Complicated appendicitis is associated with a higher incidence of major complications after appendectomy [5,6]. Major postoperative complications after appendectomy include wound infection and IAA, which are common causes of prolonged hospital stay, greater cost, and lower quality of life [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moon and his friends had showed that risen CRP level was related to complicated appendicitis (19). Also, when CRP values that were over 5 mg/dL were compared with leucocytosis, there were studies indicating that the only meaningful factor was the discrimination of complicated and non-complicated appendicitis (20). CRP values that were over 5.98 mg/dL had been obtained as meaningful for complicated appendicitis.…”
Section: Discussionmentioning
confidence: 99%